Correlation of Troponin-I with Angiographic Profile in Patients of Unstable Angina (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Objective: The study was intended to determine the angiographic profile (severity, site, and type of lesion) based on the level of cardiac troponin-I (cTn-I) in patients of unstable angina.Methods: The present cross-sectional study was conducted in the Department of Cardiology, Sir Salimullah Medical College & Mitford Hospital (SSMCH). Data were collected at Ibrahim Cardiac Hospital & Research Institute and SSMCH. A total of 81 patients with unstable angina were selected over a period of 1 year. Based on the level of cTn I at admission, the patients were divided into high risk (troponin-I level 0.060.6) and low-risk (0